Analisis Pembelajaran Daring Matematika pada Siswa Kelas XII IPA SMA Negeri 7 Mataram - Mutala'ah Mutala'ah; Arjudin Arjudin; Wahidaturrahmi Wahidaturrahmi; Sudi Prayitno (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to describe the online mathematics learning process and to find out the mathematics learning outcomes in terms of the mathematics disposition of class XII IPA students at SMA Negeri 7 Mataram. This type of research is descriptive qualitative. All students of class XII IPA at SMA Negeri 7 Mataram are the population, where the sample size is 62 students who were selected by cluster random sampling rule. Data collection used a questionnaire, interview and documentation study. From this research, the results show that: (1) The learning process carried out by the teacher changes from direct learning to online learning. In the online learning process, there are several difficulties experienced by students, including students who do not understand the material presented by the teacher, whether the material is delivered in the form of a pdf or video that has been shared. In implementing the online learning process the teacher is not the only source of learning so students are actively looking for other learning reference sources such as videos on YouTube and websites. Assessment of learning outcomes is carried out by providing a written test of the test resulting in that there is no increase in student learning outcomes during learning with an online system. The implementation of online learning cannot be separated from the supervision of parents and teachers. (2) There is a correlation between final semester test scores with students' mathematical dispositions.